The Structure and Performance Analysis: Empirical Study on Commercial Banking in Indonesia 2010 – 2019 - Zahrah Zahrah; Baiq Dinna Widiyasti; Lady Faerrosa Josman (Universitas Muhammadiyah Yogyakarta, 2022)
The purpose of this paper is to conduct an empirical study about the structure and performance of the banking sector in Indonesia with several specific factors which influenced the firms and the other control variables. This study used panel data which are the secondary data, total asset, ROA, CAR, LDR, and ROE ranging from 2010 to 2019. The sources are taken for the last ten years which is from the form of bank financial statements published by Bank Indonesia and Indonesian banking statistics published by the Indonesia financial services authority as well as from annual financial statements of each bank. In order to measure structure, this paper used concentration ratio as well as HHI for four large banks, to know the performance of the firm, this study used Return on Asset data, and to analyze the relationship between structure and performance, it used simple linear regression. This paper found that Indonesian banking has a high concentration, it proved from the value of HHI is more than 2500, and the value of CR4 shows between 40% and no more than 60%. It shows that the Indonesian banking sector is an Oligopoly market. Following further, there is a negative relative between the structure and performance of the firm proving the result of regression between total assets and CR4 for ten years.